2008
DOI: 10.1111/j.1365-2133.2007.08390.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proteasome inhibitors on proliferation and apoptosis of human cutaneous melanoma-derived cell lines

Abstract: This study provides information regarding the in vitro effects of proteasome inhibitors on melanoma cell lines, and the molecular mechanisms involved. It also gives support to the future use of such inhibitors in the treatment of patients with melanoma, either administered alone or in combination with other drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 44 publications
(45 reference statements)
3
30
0
Order By: Relevance
“…20,21 The cell lines were cultured in Dulbecco's Modified Eagle Medium (DMEM) (Gibco ® Cell Culture, Barcelona, Spain) with 10% fetal calf serum (FCS; Gibco ® ) and 20 mM penicillin/ streptomycin/glutamine (Sigma-Aldrich, Madrid, Spain) at 37°C and in 5% CO 2 . The cells were trypsinized and plated in 96-well plates and incubated with octreotide or SOM230 (Novartis, Basel, Switzerland) for 1, 3 and 6 days.…”
Section: Malignant Melanoma Cell Lines and Cell Culturementioning
confidence: 99%
“…20,21 The cell lines were cultured in Dulbecco's Modified Eagle Medium (DMEM) (Gibco ® Cell Culture, Barcelona, Spain) with 10% fetal calf serum (FCS; Gibco ® ) and 20 mM penicillin/ streptomycin/glutamine (Sigma-Aldrich, Madrid, Spain) at 37°C and in 5% CO 2 . The cells were trypsinized and plated in 96-well plates and incubated with octreotide or SOM230 (Novartis, Basel, Switzerland) for 1, 3 and 6 days.…”
Section: Malignant Melanoma Cell Lines and Cell Culturementioning
confidence: 99%
“…Therefore, inhibition of proteasome activity has emerged as a new chemotherapy strategy for malignant tumors. Although studies have shown that inhibition of proteasome activity could inhibit cellular proliferation in several tumor cell lines including melanoma, prostate cancer and glioma cells [3][4][5][6] , its underlying mechanism is not fully understood. The proteasome inhibitor bortezomib has been authorized by the US Food and Drug Administration to enter clinical trials, but it is used mainly in the leukemia field.…”
Section: Introductionmentioning
confidence: 99%
“…41 Preclinical studies revealed bortezomib to be effective at inhibiting the in vitro growth of several human melanoma cell lines. 42 A phase II study of bortezomib alone in the treatment of metastatic melanoma proved to be ineffective. 43 Bortezomib may achieve better results if used in combination with chemotherapeutic drugs.…”
Section: Fibrohistiocytic Tumorsmentioning
confidence: 99%